Nanopartículas de óxido de zinco dopada com prata: alternativa para controle de bioindicadores, prevenção da formação de biofilmes e passagem de Salmonella spp. para o interior de ovos de perus - Silva, Paula Luiza Alves Pereira Andrada (2017)
Salmonella spp. is often associated with cases of human infections worldwide. The consumption of contaminated foods, especially products of poultry origin (meat and eggs), are the most associated with these cases. Control the presence of Salmonella spp. and other microorganisms in poultry production is a challenge, mainly due to the ability to produce biofilms. In this context, nanotechnology with the development of nanoparticles appears with new possibilities of control and prevention of contaminations. The objective of this study was to evaluate silver-doped zinc oxide (ZnO-Ag) nanoparticles in the control of bioindicator microorganisms, the prevention of biofilm formation and the passage of Salmonella spp. to the inside of turkey eggs. Effect of the biocidal action of the nanoparticle on the control of indicator microorganisms (mesophiles, total coliforms, Escherichia coli and molds / yeasts), reduction of the contaminating load of S. Enteretidis on biofilms in egg shells and inhibition of biofilm formation of S. Heidelberg in eggs treated with the nanoparticle prior to contamination with the bacterium. It was also verified diverse behavior among different serovars of Salmonella spp. for adhesion characteristics and formation of biofilms. Still images were generated in Confocal microscopy and scanning electron, which allowed to observe rough characteristics of the turkey egg shell structure and to show the non - interference of silver - doped zinc oxide nanoparticle on the surface of the eggshells of turkeys. The results of the ZnO-Ag nanoparticles in the control of bioindicators and Salmonella spp., in addition to the reduction in egg contamination and lower passage of Salmonella spp. to the interior of the eggs, present the ZnO-Ag nanoparticle as a potential substance for use in poultry farming. However, results are needed to demonstrate the toxicological safety of its use and the precise determination of effective doses and concentrations.